2014
DOI: 10.1186/2193-1801-3-73
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric panniculitis in a child misdiagnosed as appendicular mass: a case report and review of literature

Abstract: Mesenteric panniculitis is a chronic inflammatory process involving the adipose tissue of the mesentery. The etiology is unknown, and it is rare in children. We report a 5 year old girl who presented with abdominal symptoms and was misdiagnosed as appendicular mass. The correct diagnosis was established after surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…Similar to adults, the most common finding in children is abdominal pain, sometimes presenting as acute abdomen, leading to surgical intervention. 2,[21][22][23] Two of the cases in this paper presented with signs and symptoms of acute abdomen, one of them had a preliminary diagnoses of appendicitis resulting in surgical intervention the other patient received an explorative laparotomy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar to adults, the most common finding in children is abdominal pain, sometimes presenting as acute abdomen, leading to surgical intervention. 2,[21][22][23] Two of the cases in this paper presented with signs and symptoms of acute abdomen, one of them had a preliminary diagnoses of appendicitis resulting in surgical intervention the other patient received an explorative laparotomy.…”
Section: Discussionmentioning
confidence: 94%
“…20 It is usually benign, but intestinal obstruction, perforation, pneumoperitoneum, ischemic colitis, chylous acid, vascular thrombosis, recurrent pleural effusion, biliary and pancreatic fistula are reported complications. 21 Because of this wide variety and non-specific clinical features, mesenteric panniculitis should be in the differential diagnosis of chronic abdominal pain in cases where common causes are excluded. Physical examination, laboratory and imaging investigation may not be sufficient alone for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…n In up to 90% of cases, intraabdominal panniculitis involves the small bowel mesentery or sigmoid mesentery (mesenteric panniculitis), but on rare occasions, the region of involvement is the mesocolon, omentum, retroperitoneum or pelvis. 5 Mesenteric panniculitis is a progressive disease and has three typical grades according to histological grading: mesenteric lipodystrophy ( w h e n f a t t y d e g e n e r a t i o n a n d n e c r o s i s are predominant), mesenteric panniculitis (subsequent marked inflammatory reaction), retractile mesenteritis or mesenteric fibrosis (fibrosis of the adipose tissue). 5 M e s e n t e r i c p a n n i c u l i t i s i s u s u a l l y a s y m p t o m a t i c a n d o f t e n i n c i d e n t a l .…”
Section: Figure 3: Histopathologic Examinationmentioning
confidence: 99%
“…5 Mesenteric panniculitis is a progressive disease and has three typical grades according to histological grading: mesenteric lipodystrophy ( w h e n f a t t y d e g e n e r a t i o n a n d n e c r o s i s are predominant), mesenteric panniculitis (subsequent marked inflammatory reaction), retractile mesenteritis or mesenteric fibrosis (fibrosis of the adipose tissue). 5 M e s e n t e r i c p a n n i c u l i t i s i s u s u a l l y a s y m p t o m a t i c a n d o f t e n i n c i d e n t a l . Daskalogiannaki et al reported an incidence of 0.6% of mesenteric panniculitis among 7620 patients on CAT scan evaluation.…”
Section: Figure 3: Histopathologic Examinationmentioning
confidence: 99%